2020
DOI: 10.1002/jcla.23577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antifungal and cytotoxicity activities of titanium dioxide and zinc oxide nanoparticles with amphotericin B against different Candida species: In vitro evaluation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The antifungal effect of TiO2NPs against C. albicnas was obvious in the modified groups when compared to control group, this finding agrees with results of a study 39 who found that up to 65% of the C. albicans were killed after exposure to 100 μg/mL of TiO2NPs. A similar results was concluded with of Kermani et al 40 who found that higher percentage of the titanium and zinc oxide nanoparticles increased their toxicity. It was documented that TiO2NPs cause C. albicans yeast cell death by producing intracellular reactive oxygen species (ROS), this in turn causes oxidation of the Coenzyme-A and peroxidation of lipids which subsequently decreases respiratory activity and ultimately causes cell death 41 .…”
Section: Discussionsupporting
confidence: 89%
“…The antifungal effect of TiO2NPs against C. albicnas was obvious in the modified groups when compared to control group, this finding agrees with results of a study 39 who found that up to 65% of the C. albicans were killed after exposure to 100 μg/mL of TiO2NPs. A similar results was concluded with of Kermani et al 40 who found that higher percentage of the titanium and zinc oxide nanoparticles increased their toxicity. It was documented that TiO2NPs cause C. albicans yeast cell death by producing intracellular reactive oxygen species (ROS), this in turn causes oxidation of the Coenzyme-A and peroxidation of lipids which subsequently decreases respiratory activity and ultimately causes cell death 41 .…”
Section: Discussionsupporting
confidence: 89%
“…This demonstrates the effectiveness of ZnO nanoparticles and the tolerance of eukaryotic cells to these nanoparticles. Another In Vitro study in Iran showed that using ZnO NP against C. albicans resulted in a minimum inhibitory concentration of 128 μg/mL and a minimum fungicidal concentration of 256 μg/mL [ 59 ]. In contrast our study, using ZnO NPs at 99.18 μg/mL + 1-min UV-B had 100 % growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…CuO NPs have a major effect on fungi destructuration, while the polymer creates a biocompatible platform that sustains contact with the oral mucosa and the release of NPs [ 175 ]. Similarly, TiO 2 and ZnO NPs were studied for their antifungal activity as potential alternatives to amphotericin, but their effect was favorable at higher MIC values than the antifungal MIC [ 176 ].…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%